Impairment of quality of life due to COVID-19-induced long-term olfactory dysfunction - Winter, Anja L.; Henecke, Sofie; Lundström, Johan N.; Thunell, Evelina (Frontiers in Psychology, 2023)
Olfactory dysfunction is one of many long-lasting symptoms associated with COVID-19, estimated to affect approximately 60% of individuals and often lasting several months after infection. The associated daily life problems can cause a decreased quality of life. Here, we assessed the association between perceived quality of life and both qualitative and quantitative olfactory function (distorted and weakened sense of smell, respectively) in 58 individuals who had undergone confirmed SARS-CoV-2 infection and who complained about olfactory dysfunction. Participants with large quantitative olfactory dysfunction experienced a greater reduction in their quality of life. Moreover, our participants had a high prevalence of qualitative olfactory dysfunction (81%) with a significant correlation between qualitative olfactory dysfunction and daily life impairment. Strong drivers of low quality of life assessments were lack of enjoyment of food as well as worries related to coping with long-term dysfunctions. These results stress the clinical importance of assessing qualitative olfactory dysfunction and the need to develop relevant interventions. Given the poor self-rated quality of life observed, healthcare systems should consider developing support structures, dietary advice, and guidelines adapted to individuals experiencing qualitative olfactory dysfunction.